Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi terhadap Kinerja Karyawan Saat Pandemi Covid-19 - Nurul Fahmi Sultan; Rica Yulianti Lukman; Kartini Kartini (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2021)
This study aims to examine the effect of leadership style and organizational commitment on employee performance during the Covid-19 pandemic. The objects in this study are employees of PT Sinar Mayang Lestari. This research uses quantitative research. The population in this study were 60 employees of PT Sinar Mayang Lestari. The sampling technique in this research is saturated sample or total sampling, which is as many as 60 respondents. This study uses primary data obtained by distributing online questionnaires with the help of google forms. The data obtained were then processed using SPSS analysis tools, namely reliability test, multicollinearity test, heteroscedasticity test, normality test, and multiple regression analysis (F test, T test, and R2 test). The results of this study indicate that partially, leadership style has no effect on employee performance during the Covid-19 pandemic which is indicated by a significance level of 0.261> 0.05, while organizational commitment affects employee performance during the Covid-19 pandemic with a significance level of 0, 00 < 0.05.